REFLECTIONSON LABORDYNAMICSIN RELATION TO THE LABOR MARKET - Patricia Rosa Roman Reyes; Juan Gabino Gonzalez; Eduardo Becerril Forero Andrew Sandoval (European Scientific Journal, ESJ, 2014)
The recognition that the insertion employment of people is strongly influenced by the characteristics of the familiar unit, of which they form a part, has reinforced the interest of this study to achieve an analysis of the family job in small establishments as a way of advancing the discussion of the special features of the link work – family in specific areas of the labour activity. Based on the existence of a relationship between the work and family environment, the document proposed to deepen the various ways job participation occurswithin the family members in the small Mexican establishments, seeking to know the participation characteristics and analyse the relationship between the familiar unit andthe economic unit.